SHARIA ECONOMIC LAW ANALYSIS ON ZAKAT MANAGEMENT AT BAZNAS BANDAR LAMPUNG CITY - Zaharah, Rita; Fauzi, Mohammad Yasir (Universitas Muhammadiyah Surabaya, 2024)
This study examines the potential of zakat as an economic instrument that can enhance the welfare of the Muslim community if managed properly according to Sharia principles. In practice, zakat's collection, management, and distribution should comply with religious guidelines to be used productively as a community fund source. However, current zakat management faces challenges, such as the use of conventional banks for zakat collection, distribution that is more consumption-oriented, and a management process that is not yet effective. This research was conducted at BAZNAS in Bandar Lampung City using a descriptive qualitative approach. The results show that the use of conventional banks by BAZNAS is solely as a zakat collection medium, not as a manager, and is considered compliant with Sharia economic law, referencing Ibn Asyur's maqashid shari'ah, as it provides broad benefits. As an official zakat management institution in Bandar Lampung, BAZNAS strives to manage zakat by government regulations to improve community welfare through distribution models that include consumptive and productive empowerment approaches.